Faktor-Faktor yang Mempengaruhi Transparansi Pemerintahan Kota: Indonesia Bagian Tengah Dan Timur - Khoirunnisa Dwi Nuur Afifah; Jumaiyah Jumaiyah (SUSTAINABLE, 2026)
This study examines the determinants of city government transparency in Central and Eastern Indonesia over the period 2019–2023, focusing on four variables: government size, quality of financial reporting, administrative responsiveness, and political environment. Using ordinal logistic regression on secondary data from 21 city governments (105 observations), the findings reveal that government size has a positive and significant effect on city government transparency (β = 0.725, p = 0.002), indicating that larger governments with greater institutional capacity are more likely to achieve higher levels of transparency. In contrast, financial reporting quality (p = 0.713), administrative responsiveness (p = 0.404), and political environment (p = 0.757) do not exert statistically significant effects on transparency. These results imply that city government transparency in Central and Eastern Indonesia is driven more by structural and institutional capacity than by administrative performance or political conditions. The originality of this study lies in its focus on the underexplored context of Central and Eastern Indonesian cities using ordinal logistic regression to capture hierarchical variation in transparency levels, demonstrating that institutional capacity—not administrative compliance or political dynamics—is the primary determinant of public information disclosure in resource-constrained regions. Policymakers should prioritize strengthening institutional capacity, human resource development, and digital infrastructure to enhance transparency at the local government level.